1978
DOI: 10.1136/hrt.40.12.1356
|View full text |Cite
|
Sign up to set email alerts
|

Effect on survival after myocardial infarction of long-term treatment with phenytoin.

Abstract: 51 and 75 per cent of subjects at any one follow up visit. There were 19 withdrawals from the treatment group, 10 of which were the result of side effects. There were 5 withdrawals from the control group. According to the original intention to treat, there were 18 deaths at 2 years in the treatment group and 14 deaths in the control group. There was no reduction in the incidence of instantaneous or sudden deaths. Deaths on treatment were not associated with a low phenytoin plasma level. Phenytoin treatment sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

1979
1979
1993
1993

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…The subjects were drawn from a larger prospective, controlled trial designed to evaluate the prophylactic use of DPH after myocardial infarction (Peter et al, 1978). The details of the patient groups, the method of monitoring DPH treatment and the details of other drug treatment are recorded in previous publications (Heyma et al.…”
Section: Subjects a N D Methodsmentioning
confidence: 99%
“…The subjects were drawn from a larger prospective, controlled trial designed to evaluate the prophylactic use of DPH after myocardial infarction (Peter et al, 1978). The details of the patient groups, the method of monitoring DPH treatment and the details of other drug treatment are recorded in previous publications (Heyma et al.…”
Section: Subjects a N D Methodsmentioning
confidence: 99%
“…The study was incorporated into a prospective trial investigating the prophylactic value of DPH after myocardial infarction (Peter et al, 1978). After hospital admission with a myocardial infarction patients were stratified according to sex, age in years (less than 40, 40-55, 56-70) and the presence or absence of a past history of myocardial infarction.…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
“…The DPH-treated group received DPH for approximately 2 years, individual dosages being adjusted when necessary at intervals, with the aim of maintaining plasma levels of the drug in the range 40-80 pnol/l, which is generally regarded as therapeutic for treatment of epilepsy and has been suggested for the management of cardiac arrhythmias (Bigger et ul., 1968). Details of the protocol for DPH treatment and monitoring of its plasma levels are published elsewhere (Peter et al, 1978). The subject data are shown in Table 1.…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
“…'0 However, it has been well established by several large studies that VPDs contribute independently to the risk of overall mortality and sudden death.1-5 [7][8][9] See p 928 Six randomized, controlled trials of long-term antiarrhythmic therapy after AMI were reported before 1981. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] None of the trials demonstrated a benefit; three showed a trend against the study drug. Reviews of these trials17'8 point to the problems of inadequate sample size, failure to select high-risk patients, and the use of drugs with relatively low antiarrhythmic potency.…”
mentioning
confidence: 99%